Educational technology for disseminating Islamic values: A systematic literature review and bibliometric analysis - Trimulyo, Agus; Al Kodri; Aldiyansah, Muhammad; Anas, Ahmad; Basith, Abdul; Yahya, Ahmad; Haq, Muhammad A’inul; Afriansyah, Dibi; Al Husna, Lathifah; Mukarom, Arik Maghfirotul (Research Journal in Advanced Humanities, 2026)
The rapid advancement of digital technologies has transformed how religious knowledge is produced, accessed, and disseminated, including within Islamic education through digital learning environments, social media platforms, and emerging intelligent systems. However, existing research on the use of educational technology to disseminate Islamic values remains fragmented across different technological approaches, educational contexts, and disciplinary perspectives. This study aims to systematically review the literature on the use of educational technology in disseminating Islamic values and to identify research trends, technological categories, pedagogical practices, and learning impacts within this field. A systematic literature review (SLR) was conducted following the PRISMA framework to ensure methodological transparency and rigor. A total of 207 articles published between 2015 and 2026 were included for bibliometric analysis. From this dataset, 30 articles were further analyzed through qualitative content analysis to examine the types of technologies employed, modes of technology utilization, and their impacts on Islamic learning outcomes. Bibliometric analysis was performed using the Biblioshiny interface of the bibliometrix R package to map publication trends, research productivity, collaboration patterns, and thematic structures. The findings reveal a substantial growth in research output over the past decade, with Indonesia and Malaysia emerging as the most productive countries. Thematic and keyword network analyses indicate that the research field is structured around three major themes: Islamic education as the conceptual foundation, social media–based digital da’wah as the dominant communication channel, and emerging technologies such as artificial intelligence as an expanding research frontier. Content analysis further identifies five major categories of educational technologies used to disseminate Islamic values: social media platforms, artificial intelligence–based systems, institutional digital learning systems, multimedia learning technologies, and mobile-based religious applications. These technologies contribute to learning outcomes across cognitive, affective, behavioral, and social dimensions, although challenges related to misinformation, fragmented religious understanding, and digital literacy remain important concerns.